Pengaruh Live Streaming, Flash Sale, Dan Online Customer Review Terhadap Keputusan Pembelian Brand Lokal Tas Di Tiktok Shop - Choirunnisa, Alya; Wahono, Budi; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze the influence of Live Streaming, Flash Sale, and Online Customer Review on the purchasing decision of local bag brands on TikTok Shop. Specifically, this research evaluates the impact of these three variables both simultaneously and partially on purchasing decisions. The research method used is quantitative with an explanatory research design. The sample consists of 87 respondents, namely students from the Faculty of Economics and Business at Universitas Islam Malang, class of 2020, who have made purchases of local bag brands on TikTok Shop. Primary data was collected through questionnaires.The results of the study indicate that simultaneously, the variables of Live Streaming, Flash Sale, and Online Customer Review have a significant effect on purchasing decisions, with an adjusted R² value of 0.353, meaning that 35.3% of purchasing decisions are influenced by these three variables. Partially, Live Streaming has a significant effect on purchasing decisions (significance value 0.002 < 0.05). However, Flash Sale (significance value 0.071 > 0.05) and Online Customer Review (significance value 0.749 > 0.05) do not show significant partial effects. Keywords : Live Streaming, Flash Sale, Online Customer Review, Purchasing Decision